Effect of Exchange Rate and Global Index in Five Countries Against CSPI - Mulyadi Mulyadi (DINASTI RESEARCH, 2020)
This study aimed to determine the correlation between Exchange Rate and Global Index on Composite Stock Price Index in Indonesia Stock Exchange in 2014-2019 partially and simultaneously. Exchange Rate and Global Index is proxied by five countries namely Hong Kong, Japan, USA, Singapore, and China. The data used is secondary data obtained through the Official Website of Bank Indonesia for variable Exchange Rate, Official Website Yahoo Finance and Official Website Investing.com for variable Global Index. The methods of data analysis used is multiple linear regression. The results showed that the HKD, JPY, USD, SGD, CNY, and STI partially insignificant on CSPI, as well as HSI and DJIA partially positive effect significant on CSPI, while N225 and SSEC partially negative effect significant on CSPI. Simultaneously, all the variables have a significant effect by influencing by 93.9% while the remaining 6.1% is explained by other variables not examined in this study.